INTERNALISASI NILAI KARAKTER SISWA MELALUI PROGRAM PEMBIASAAN PEMBACAAN ASMAUL HUSNA DI SDN UMBUL KAPUK - Ely Sholihah, - (2022)
The depravity of the nation's children can be seen from the morals that are starting to fade, it can be observed in how they talk to someone, both teachers and even their parents, dirty sentences, and bad morals. Therefore, must have an effort in handling and even prevent these events so as not to form a culture in children. The efforts that can be done is by getting children to do good deeds. Character education in schools can be made through habituation of incidental and routine activities which are expected to grow good character values embedded in children. Due to the importance of forming student character values, schools have implemented student character development through the habituation method, namely at SD Negeri Umbul Kapuk. This research was made to know the process of habituation, the character values contained in the habit of reading Asmaul Husna, and its implications. Uses a qualitative approach with case study research methods and the types of auxiliary instruments used are observation, interview sheets, questionnaires, and documentation. The results of the analysis carried out by researchers, character building of students through the method of habituation of reading Asmaul Husna at SD Negeri Umbul Kapuk include: religious, fond of reading, responsibility, discipline, independent, friendly/communicative, social care, peace-loving, tolerance, and curiosity. know. The implication of this habituation resulted in a questionnaire that 78% of students answered correctly and 22% answered incorrectly. The correct answer is the expected response according to the statement in the questionnaire regarding the student's character value. Referring the number of correct responses, namely 78%, the value of the character of the nation's children is already attached to students. These are effective efforts to build a character that is applied by the Umbul Kapuk Public Elementary School to students in grades 4, 5, and 6.